The 4 routes to entrepreneurial success - Miner, John B. (Berrett-Koehler Publishers, 1996)
John Miner details four personality types that characterize successful entrepreneurs - Personal Achievers, Supersalespeople, Real Managers, and Expert Idea Generator then shows you how to use this information to map out your own path to success. Based on 20 years of research and a systematic seven-year study of 100 entrepreneurs, The 4 Routes to Entrepreneurial Success details the distinctive characteristics of each type and explains why they succeed or fail. Using Miner's self-assessment questionnaire you'll discover whether you possess the talents, skills, and characteristics it takes to start and run your own business. The results will help you determine how you can be successful as an entrepreneur.